2003
DOI: 10.1118/1.1573891
|View full text |Cite
|
Sign up to set email alerts
|

An EGSnrc investigation of cavity theory for ion chambers measuring air kerma

Abstract: The EGSnrc system is used to compare the response of an aluminum-walled thimble chamber to that of a graphite-walled thimble chamber for a 60Co beam. When compared to previous experimental results, the EGSnrc values of the ratios of chamber response differ by as much as 0.7% from the experiment. However, it is shown that this difference can be more than accounted for by switching from using the graphite mean excitation energy of 78 eV used in dosimetry protocols to the value of 86.8 eV suggested by more recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 18 publications
2
28
0
Order By: Relevance
“…Similarly, stoppingpower ratios computed using the user-code SPRRZnrc, agree to within 0.1% of TG-51 values. A previous study 31 has shown that values of ␣ used in the TG-51 protocol agree well with the EGSnrc values for the wall thicknesses considered here. Since EGSnrc values for the dosimetry parameters used in Eq.…”
Section: B Values Of P Wall In Photon Beamssupporting
confidence: 81%
“…Similarly, stoppingpower ratios computed using the user-code SPRRZnrc, agree to within 0.1% of TG-51 values. A previous study 31 has shown that values of ␣ used in the TG-51 protocol agree well with the EGSnrc values for the wall thicknesses considered here. Since EGSnrc values for the dosimetry parameters used in Eq.…”
Section: B Values Of P Wall In Photon Beamssupporting
confidence: 81%
“…A calculation using CSnrc results in a value of D gr / D Al = 0.9927± 0.0001. This compares with, but shows much lower uncertainty than, a previous CAVRZnrc calculation 24 and with an EGS4/PRESTA correlated sampling calculation 7 that gave values of 0.9937± 0.0010 and 0.9942± 0.0013, respectively. It also agrees with the measured result of 0.992± 0.002 from Palm and Mattsson.…”
Section: Efficiency Gainsupporting
confidence: 47%
“…In previous investigations, it was shown that, combined, the density effect and I value of graphite can have a large effect ͑i.e., 1.5% or more͒ on the calculated response of graphite chambers 6 and on calculations of the SA graphiteto-air stopping-power ratio. 3 Although these large effects likely cancel when computing values of K fl , the effects of both the density and I value on K fl were examined at the level of statistical uncertainty considered here.…”
Section: Iiih1 Effect Of Density and Mean Ionization Energy On K Fmentioning
confidence: 99%
“…Their calculated values of K SA ranged between 0.9970 and 1.0005 for a 60 Co beam depending on the chamber and the value of low-energy cutoff ⌬ used in the calculation of stopping-power ratio. Buckley et al 6 later showed that K SA is unity for one particular graphite thimble chamber at 60 Co energies but is a 0.5% correction ͑1.0050Ϯ 0.0003͒ for the same chamber configured with an aluminum thimble. However, neither study determined whether the K SA correction was due to fluence perturbations by the cavity or due to the wrong choice of ⌬ in the calculation of the SA stopping-power ratio since, as we discuss in the following sections, this requires an indepth knowledge of how K SA is affected by changes in chamber wall material and cavity dimension.…”
Section: Introductionmentioning
confidence: 99%